Life cycle assessment (LCA) for apple orchard production systems including low and high productive years in conventional, integrated and organic farms. (May 2017) - Goossens, Y.; Annaert, B.; De Tavernier, J.; Mathijs, E.; Keulemans, W.; Geeraerd, A.
Abstract: Several papers highlight methodological challenges related to the lifecycle assessment (LCA) of fruit production systems. These concern both the limited number of impact categories assessed in current LCA literature and the narrow view on the full production phase of an orchard cycle. This article addresses these challenges and contributes to improving the scientific knowledge on impacts associated with less productive years within an orchard cycle, and how these affect the impact associated with an entire fruit growing cycle. Using apple as a case study, an LCA is performed to obtain the impacts associated with young and old low productive trees, alongside those associated with trees in full production. Using the ILCD impact assessment method, the LCA is based on a large dataset of apple orchards in Flanders (Belgium), covering three production systems (conventional, integrated and organic production) and accounting for input and yield variability. The annual median impact values are used to describe a "typical" orchard for each orchard phase and production system. In conventional farming, lowest annual median impacts are mostly found in the full production phase while highest impacts are observed in the old low productive orchards. In integrated and organic production on the other hand, the lowest annual median impacts mostly occur in the old low productive orchards while highest impacts are found for the young low productive trees. Results for organic farming must however be interpreted with care, following the small sample size of organic producers. To calculate the impacts associated with a full orchard cycle, an orchard model was built based on the annual median impact within each apple bearing orchard phase and production system and using weighting factors based on the yields obtained within each of the orchard phases. Across the three production systems, the two low production phases are responsible for 27 to 38% of the calculated orchard cycle impact. Calculated impacts for the entire orchard cycle are, on average across the impact categories, higher than full production impacts in conventional and integrated farming, while lower in the case of organic farming. A mere focus on high productive trees leads to an underestimation of, on average, 18% in conventional farming and 11% integrated farming, versus an overestimation of 11% for organic farming. Inclusion of non-productive phases such as nursery and planting and destruction of the orchard, would further alter the orchard cycle impacts. Highlights: LCA of large dataset with conventional, integrated and organic apple orchards 3 Focus on both high and low productive years within orchard cycle 4 Orchard phase with lowest and highest impacts (per t) depends on production system 5 Focus on high productive trees: under- or overestimation of orchard cycle impacts 6 Underestimation for conventional & integrated orchards; overestimation for organic